Myoglobin redox form stabilization: role of metabolic intermediates and NIR detection - Mohan, Anand (Kansas State University, 2009)
Several experiments were conducted to evaluate factors affecting myoglobin redox forms stability and detection of myoglobin redox forms using near infrared (NIR) spectroscopy. In experiment 1, we investigated the relationship between metmyoglobin (MMb) reduction and oxidation of malate to α-ketoglutarate with regeneration of reduced nicotinamide adenine dinucleotide (NADH) via malate dehydrogenase (MDH). Our specific objectives for this experiment were: (1) to examine the interaction of malate and MDH to reduce MMb in vitro, (2) to determine the influence of pH, temperature, NAD[superscript]+, and malate concentration on MDH enzyme activity and MMb reduction, and (3) to determine the effects of malate on NADH generation, metmyoglobin reducing activity, and color stability using beef muscles (Longissimus lumborum, Psoas major, and Semitendinosus) extracts. We observed that, nonenzymatic reduction of horse MMb in vitro in a malate-MDH-NADH system increased with increasing NAD[superscript]+ and L-malate concentrations. Our findings further confirmed that reduction of MMb in beef extract was NAD[superscript]+ and malate concentration dependent (p < 0.05). A model system was described for studying mechanisms of enzymatic reduction of metmyoglobin reduction as a means to improve meat color and the results support the hypothesis that malate can replenish NADH via MDH activity, ultimately resulting in stabilizing myoglobin redox chemistry.In experiment 2, we assessed the ability of mitochondrial and cytoplasmic malate dehydrogenase present in postrigor bovine skeletal muscle to utilize malate as fuel for NADH regeneration and MMb reduction via the malate-NAD-MMb system. Furthermore, addition of lactate to beef mitochondrial and cytoplasmic isolates was evaluated to determine if interactions between malate and lactate increased MMb reduction. Addition of malate to isolated beef mitochondrial and cytoplasmic isolates at pH 7.2 increased (p < 0.05) MMb reduction. MMb reduction resulting from the addition of malate and lactate was equal or greater than MMb reduction resulting from malate alone. The findings from this study provided evidence that mitochondria and cytoplasmic proteins isolated from beef skeletal muscles of different metabolic origin differ substantially in their enzymatic composition. Malate-MDH assisted-MMb reduction using Mitochondrial and cytoplasmic isolates from the three beef skeletal muscles exhibited substantial differences in enzymatic compositions and their ability to reduce MMb in vitro. Differences were also observed in the enzymatic characteristics of MDH-assisted-MMb among the three beef muscles. In experiment 3, we investigated the effects of three glycolytic and tricarboxylic acid cycle metabolites on myoglobin redox forms and their in influence on meat color stability. Eighteen combinations of malate (M), lactate (L), and pyruvate (P) were added to beef Longissimus lumborum, Psoas major, and Semitendinosus muscle homogenates to study their effects on metmyoglobin formation during incubation at 25 °C. Changes in surface color at 0, 2, 4, 8, and 12 hrs were evaluated using refecto-spectrophotometry [both L*a*b* and wavelengths specific for MMb]. Results from this study suggests that at 2% concentrations level of the individual metabolites (M, L, or P), the most effective metabolite at retarding MMb formation was L > M > P in the ST, and M > L > P in the PM and LL muscles. MMB was reduced most effectively with combination of metabolites where M+L > M+P > L+P. Enhancement of meat with these metabolites can effectively extend color life of postrigor meat apparently by providing more reducing conditions for myoglobin, thus increasing myoglobin redox form stability. Experiment 4 was conducted to determine how near-infrared (NIR) tissue oximeter measurements of post-rigor beef skeletal muscle relate with the more established methods of quantifying myoglobin redox states. Surface color differences were created by packaging steaks in vacuum (VAC), 80% O[subscript]2 and 20% CO[subscript]2 modified atmosphere packaging (HiOx MAP), polyvinyl chloride film overwrap (PVC), and HiOx MAP converted to PVC (HiOx-PVC) after 2 days. Changes in surface color and sub-surface pigments during display (0,2, 4, 10, and 15 days at 2 °C) were characterized by using a reflectance-spectrophotometer and a near-infrared tissue oximeter, respectively. Fiber orientation, storage, and packaging affected (p < 0.05) color, total pigment, deoxymyoglobin, and oxymyoglobin content. Tissue oximetry measurements appear to have potential for real-time monitoring of myoglobin redox forms and oxygen status of packaged meat, but fiber orientation needs to be controlled. In experiment 5, we investigated the response of frequency-domain multidistance (FDMD) NIR tissue oximetry for detecting absolute amounts of myoglobin (Mb) redox forms and their relationship to meat color stability. Four packaging formats were used to create different blends of Mb redox forms and meat colors during display. Changes in surface color and subsurface pigment forms during simulated display (0, 2, 4, and 10 d at 2 °C) were evaluated using surface reflecto-spectrophotometry (both L*a*b* and specific wavelengths) and FDMD NIR tissue oximetry. Data for both methods of direct measurement of oxymyoglobin and deoxymyoglobin were strongly related and accounted for 86 to 94% of the display variation in meat color. Indirect estimates of metmyoglobin ranged from r[superscript]2 = 59 to 85%. It appears that NIR tissue oximetry has potential as a noninvasive, rapid method for the assessment of meat color traits and may help improve our understanding of meat color chemistry in post-rigor skeletal muscle.
Keywords: myoglobin; malate; lactate; pyruvate; malate dehydrogenase; Agriculture, Food Science and Technology (0359)